Crucial skills : an anger management and problem solving teaching programme for high school students - Johnson, Penny, 1960- (Lucky Duck Bks., 1999)
This programme is aimed at students (aged 11 to 16) with challenging and angry behaviours leading to disaffection and disciplinary problems. The book includes teacher notes, lesson plans and photocopiable resources.